Experiment to search for P- and T-violating interactions in the hyperfine structure of thallium fluoride - Hinds,EA; Sandars,PGH (Physical Review A, 1980)
The authors describe a molecular-beam-resonance experiment to search for P- and T-violating interactions in the thallium fluoride molecule. Specifically the interactions looked for are of the form HPT=d TlTlF, where d is a coupling constant, Tl is a unit vector parallel to the spin angular momentum of the thallium nucleus, and TlF is a unit vector along the internuclear axis. The null result of the experiment is dh=1142 mHz. This result implies new upper limits on the electric dipole moment of the proton and on a possible weak, P- and T-violating, neutral-current tensor interaction. © 1980 The American Physical Society.